2022
DOI: 10.1002/mrm.29531
|View full text |Cite
|
Sign up to set email alerts
|

Motion‐robust, blood‐suppressed, reduced‐distortion diffusion MRI of the liver

Abstract: Purpose To evaluate feasibility and reproducibility of liver diffusion‐weighted (DW) MRI using cardiac‐motion‐robust, blood‐suppressed, reduced‐distortion techniques. Methods DW‐MRI data were acquired at 3T in an anatomically accurate liver phantom including controlled pulsatile motion, in eight healthy volunteers and four patients with known or suspected liver metastases. Standard monopolar and motion‐robust (M1‐nulled, and M1‐optimized) DW gradient waveforms were each acquired with single‐shot echo‐planar im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…Geng et al [ 22 ] showed that gradient waveforms with small M 1 values combined with segmented echo planar readouts are well-suited to obtain low-distortion images without a large influence from motion artifacts in liver DWI. The application of small M 2 values may be an interesting further step in this regard.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Geng et al [ 22 ] showed that gradient waveforms with small M 1 values combined with segmented echo planar readouts are well-suited to obtain low-distortion images without a large influence from motion artifacts in liver DWI. The application of small M 2 values may be an interesting further step in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, an aim was to minimize the echo time for each diffusion encoding separately [ 16 , 22 , 23 ]. For example, Aliotta et al proposed the CODE optimization algorithm to create asymmetric motion-compensated waveforms and demonstrated a significant reduction in the echo time [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of M1-nulled diffusion encoding has been shown for cardiac triggering in the heart 19 and pancreas, 20 respiratory triggering in renal imaging, 21 and free-breathing, 22 and breath-holding in the liver. 23 The twice refocused preparation that satisfies the Carr-Purcell-Meiboom-Gill (CPMG) condition has reduced B1 sensitivity compared to single refocusing schemes, 24 and little echo time penalty compared to single refocused M1-nulled waveforms. A magnetization prepared approach was selected to achieve diffusion weighting over DW steady-state sequences which have an oscillating signal amplitude from motion and large gradient areas.…”
Section: Image Encoding and Diffusion Contrastmentioning
confidence: 99%
“…The spleen moves relatively little during respiration, and will have fewer cycles of imparted phase from diffusion gradients compared to the pancreas, which is susceptible to cardiac motion. 6 velocity-or acceleration-compensated diffusion encoding [28][29][30][31][32][33] reduces the resolution of the imparted phase for a modest TE penalty. The imparted phase also depends on the method used for managing respiratory motion.…”
Section: 31mentioning
confidence: 99%